Antecedents of internationalisation of indigenous-owned SMEs in South Africa - Sono, Thabe Johannes Godfrey (My University, 2018)
Target Journal: The Southern African Journal of Entrepreneurship and Small Business Management Background: There is an increasing interest in indigenous entrepreneurship as a tool that can be used to address the triple challenge of poverty, inequality and unemployment. Indigenous entrepreneurs want to participate in the new global economy, but literature has found that Indigenous entrepreneurs are profoundly affected by their traditional sociocultural context which may facilitate or hinder their success in the new global economy. This study investigates the influence of factors in this traditional sociocultural context in the internationalisation of Indigenous entrepreneurs. Aim: The aim of the study was to investigate and explain the influence of three dependent variables: locality, resource capability, and cultural capital on an independent variable: internationalisation of SMEs in South Africa in the context of Indigenous entrepreneurs. Setting: The study took place in South Africa Methods: Using an online survey, a cross-sectional quantitative study was adopted on a sample of 72 Indigenous-owned SMEs to test hypothesised links between locality, resource capability and cultural capital and the internationalisation of the Indigenous-owned SMEs. Results: The study reveals some pertinent insights in the quest by Indigenous entrepreneurs to participate meaningfully in the new global economy. There is strong evidence that local resources are important to Indigenous entrepreneurs as their business leverages and benefits from these local resources and that the local environment influences the performance of their business. This means they tend to be influenced by their local environment in decisions to do with participation in the new global economy. This is not a departure from literature, iii particularly the development framework and regulation theory. The study also identifies a number of antecedents to successful internationalisation by Indigenous entrepreneurs. Conclusion: The research findings give credence to the efficacy of regulation theory and the development framework. This suggests that Indigenous entrepreneurs are not opposed to development but would like to participate in development which is respectful of their heritage. They leverage on their Indigenous cultural heritage and resources to enter into the new global economy. Indigenous entrepreneurs internationalise their operations through various entry modes such as equity and non-equity venture models but there is growing but sparse literature on the role of strategic alliances as a preferred mode of entry.
MBA
Keywords: Small business -- South Africa. Entrepreneurship -- South Africa. Business enterprises -- South Africa.